Digital strategies for managing agricultural lands in the region - Idigova Lalita; Chaplaev Huseyn; Markaryan Varvara (BIO Web of Conferences)
The article is devoted to the development of innovative digital strategies for land management in the region based on the assessment of the effectiveness of agricultural land management in agricultural organizations of the Chechen Republic. The relevance is that the influence of innovative, digital and engineering technologies in the realities of today are a factor in the intensive development of agriculture and are important for the sustainable development of rural areas and the ability to manage agricultural land. The issues of innovation based on digitalization of agricultural land management are currently still quite unexplored. The term “digital agriculture” is focused on improving rural areas and improving the quality of life in rural areas. These problems are still relevant today. The article describes the features, problems and opportunities of digitalization as a tool for the formation of innovative infrastructure in the agro- industrial complex of the Chechen Republic. The article provides an analysis of the essence of the digital development of the agricultural industry. Objective and subjective reasons hindering their development have been identified. The conducted research made it possible to formulate priority directions and strategic approaches to the formation of innovative infrastructure in the agro-industrial complex of the region.